Employer Size and Success in Manpower Training Programs for the Disadvantaged : A Dual Labor Market Analysis - Fottler, Myron (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1974)
Manpower training programs for the disadvantaged in the United States have been shifting in emphasis over time from institutional to on-the-job training. As a result, it has become increasingly important for program administrators to place trainees in the private sector. Yet little is known about employer characteristics whish are conducive or not conducive to a successful experience. The data presented here indicates that larger compagnies are significantly more successful in these programs than are smaller compagnies.